On the localization of the riesz means of multiple fourier series of distributions - Rakhimov, Abdumalik (Hindawi Publishing Corporation, 2011)
We study special partial sums of multiple Fourier series of distributions. We obtain sufficient conditions of summation of Riesz means of Fourier expansions of distributions with compact support. Copyright © 2011 A.A.Rakhimov.